Prevention of Criminal Offenses as One of the Tasks of Criminal Proceedings - A. V. Ros; R. M. Balats (Law and Safety)
The topical problem of preventing criminal offenses as a task of criminal proceedings has been studied. It has been established that the current state of crime in Ukraine and the negative tendencies that have occurred in the process of its development in modern conditions, in particular the growing number of criminal offenses, necessitates scientific and practical research to combat these socially dangerous phenomena, including in regard to the forms, methods and means of their prevention. The emphasis has been placed on crime prevention as the most socially dangerous acts. The historical development of crime prevention at different stages of society development has been studied. The author has analyzed regulatory acts of Ukraine, which contain the tasks on preventing criminal offenses within criminal proceedings. Certain terms have been defined, in particular: “prevention”, “preventive activities”, “cessation of criminal offenses and their relationship”. The author of the article hold the view that all the specified terms have a common feature, which is to carry out actions that prevent the commission of criminal offenses. The concept of “prevention of criminal offenses during the pre-trial investigation” has been formulated, which should be understood as the activities of investigators, interrogators, prosecutors aimed at applying certain procedural measures provided by the Criminal Procedural Code of Ukraine in order to prevent a person suspected of committing a criminal offense to commit criminally illegal or other actions that could destabilize the investigation of criminal proceedings. It has been concluded that it is necessary to further improve the functions of investigators (interrogators) on preventive activities during the pre-trial investigation of criminal proceedings to eliminate the identified causes and conditions that contributed to the commission of a criminal offense as one of the tasks of criminal proceedings.